Diagnostic yield of CT pulmonary angiography in the diagnosis of pulmonary embolism: A single center experience - Sun, Zhonghua; Lei, J. (Future Medicine Ltd, 2017)
The purpose of this study was to investigate the clinical application of computed tomography pulmonary angiography (CTPA) in patients with suspected pulmonary embolism (PE) based on a single-center experience. Medical records and radiological reports of 450 patients (272 men and 178 women; mean age 58.9 years; range 14-95 years) with suspected PE who underwent CTPA and triple rule-out CT scans over a period of 6 months were retrospectively reviewed. Prevalence of PE was analysed to determine the diagnostic yield of CT in these two scanning protocols. Of 450 patient records, the positive rate of PE was 30.7%. Triple rule-out CT protocol was performed in 75 out of 450 patients with the diagnostic yield of PE being only 8% (6 out of 75 patients had PE), which is significantly lower than the 35.2% as shown in the CTPA group (132 out of 375 had PE). Mean effective dose was 2.8±2.6 mSv and 13.5±7.8 mSv for CTPA and triple rule-out protocols, respectively. This study shows that CTPA has high diagnostic yield in the diagnosis of pulmonary embolism, hence justifying its appropriateness as a routine imaging modality. However, triple rule-out CT is not recommended due to the low diagnostic yield. Further reduction in radiation and contrast medium doses is necessary.